2022
DOI: 10.1093/ofid/ofac260
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccine Uptake and Factors Associated With Being Unvaccinated Among Lesbian, Gay, Bisexual, Transgender, Queer, and Other Sexual Identities (LGBTQ+) New Yorkers

Abstract: Routine data on vaccine uptake are not disaggregated by lesbian, gay, bisexual, transgender, queer, and other sexual identities (LGBTQ+) populations, despite higher risk of infection and severe disease. We found comparable vaccination uptake patterns among 1032 LGBTQ+ New Yorkers and the general population. We identified critical socioeconomic factors that were associated with vaccine hesitancy in this economically vulnerable population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…While heterosexual individuals had a higher prevalence of vaccination intention compared to sexual minority participants when aggregated, further analysis of disaggregated sexual orientation showed a higher likelihood of vaccination among gay individuals compared to heterosexual, bisexual, and lesbian participants—with heterosexual participants having a higher prevalence than bisexual and lesbian participants. These findings mirror the variability in vaccination intention across sexual orientations found in previous studies [ 13 , 35 ]. As such, there may be vaccination disparities across sexual orientation groups and, thus, a need to tailor vaccination information, campaigns, and resources to the heterogeneity of sexual minority communities.…”
Section: Discussionsupporting
confidence: 89%
“…While heterosexual individuals had a higher prevalence of vaccination intention compared to sexual minority participants when aggregated, further analysis of disaggregated sexual orientation showed a higher likelihood of vaccination among gay individuals compared to heterosexual, bisexual, and lesbian participants—with heterosexual participants having a higher prevalence than bisexual and lesbian participants. These findings mirror the variability in vaccination intention across sexual orientations found in previous studies [ 13 , 35 ]. As such, there may be vaccination disparities across sexual orientation groups and, thus, a need to tailor vaccination information, campaigns, and resources to the heterogeneity of sexual minority communities.…”
Section: Discussionsupporting
confidence: 89%
“…Two studies, both focusing on LGBT or LGBTQ+ adults in the United States, considered sex and gender as separate variables in their analysis. Low et al (2022) reported no differences based on sex assigned at birth (categorised as female, male and intersex) or gender identity (categorised as cisgender and transgender/nonbinary/other gender minority) [ 41 ]. McNaghten et al (2022) reported higher vaccination among females than males, but no difference based on gender identity (dichotomously categorised as transgender/nonbinary or not) [ 42 ].…”
Section: Resultsmentioning
confidence: 99%
“…The vaccine coverage in our study was higher than that in the USA, which reported 85.4% uptake among gay/lesbian adults and 75.7% uptake among TG adults 10 ) . Low et al reported that 81% of LGBTQ+ participants received one or more doses of COVID-19 vaccine in New York city 11 ) . Studies from Australia reported a lower coverage of 28%–57.2% among gay and bisexual men 17 , 18 ) .…”
Section: Discussionmentioning
confidence: 99%
“…They also reported a 75.7% uptake among transgender adults 10 ) . Low et al reported a similar vaccine uptake of 81% among adults who identified as lesbian, gay, bisexual, transgender, queer, and other sexual identities (LGBTQ+) in New York city 11 ) . Another study conducted in USA in early 2021 reported a moderately high acceptance of COVID-19 vaccine among sexual/gender minority men and TG women 9 ) .…”
Section: Introductionmentioning
confidence: 98%